935 Stridor in Multiple System Atrophy: An Otolaryngologist Perspective. (4th May 2021) - Cameron, M; Al, M; Jain, A; De Silva, R
Abstract: Background: Bilateral vocal cord paralysis is a rare emergency presentation for Parkinson's disease (PD) but an acknowledged complication of an atypical rarer form of PD called Multi system atrophy ( MSA). MSA is a neurodegenerative disorder comprising of autononic failure, cerebellar ataxia and parkinsonism. An early occurence of stridor can indicate a shorten survival and quality of life remains uncertain. Airway definitive management of this patient group can pose a dilemma for the Otolaryngologist who may be asked to provide a specialist opinion. Case: We present a case of a 73 year old female who developed mild stridor, hours after an emergency right sided hemiarthroplasty. On day 23 of her admission, there was a sudden airway deteoriation. The otolaryngology and anasthetic emergency team stablised her conservatively with an option of non invasive ventilation. Bilateral vocal cord palsy was observed on nasendoscopy On day 27, she was eventually diagnosed with MSA and showed partial response to a trial of madopar. Both options of a tracheostomy and laser cordotomy were avoided. She was safely discharged with follow up. Conclusions: There remains gaps in the literature towards an unaminous consensus on stridor management in MSA patients. However, raising awareness of this patient groups will strenghten decision making processes.